(untitled) (Forum Penelitian Agro Ekonomi, 2023)
Due to the pandemic and geopolitical factors worsening and threatening global food security, decreasing food waste is a problem for all nations. All nations concur that completing Sustainable Development Goals (SDG) 12.3 is vital because it affects accomplishing other goals. The difficulties caused by food waste are highly complicated, and the solutions vary across countries and policies. The paper aimed to evaluate global food waste reduction policies and generate policy recommendations for Indonesia. In order to promote a beneficial policy, several alternative policies are developed. The research method used is a qualitative approach with literature study and observation. Many policies are established to identify effective policy recommendations, and the cost of implementing the policy is minimal. The following policy recommendations should be implemented in Indonesia based on the lessons learned from other nations about the reduction of food waste and alternative policies: Improving the management of food waste from households; promoting public education; fostering collaboration between government affairs administrators in upstream and downstream agriculture; innovation and implementation of agricultural standards; digitalization; strengthening infrastructure; and enhancing collaboration with other agriculture stakeholders.